Automatic rectification of warped Bangla document images. Issue 1 (1st January 2020) - Garai, Arpan; Biswas, Samit; Mandal, Sekhar; Chaudhuri, Bidyut B.
Abstract : In this study, a robust algorithm for dewarping of camera‐captured document images, mainly in Bangla script, is proposed. The algorithm can handle various types of warped document images and they are generated due to different types of document surfaces (convex, concave or multi‐folded). The proposed algorithm is independent of font type, font size, font style and camera view angle. After initial preprocessing, the method first demarcates the text lines present in the document image. Then, the headline ( shirorekha ) position of each text line is estimated. Based on the headline position and shape, each text line is dewarped. If the document is highly warped, distorted text (e.g. thinner and shorter characters) is generated after dewarping. Special care has been taken to minimise this distortion based on most undistorted character information. Exhaustive testing shows the robustness and shape improvement of the proposed algorithm. Finally, for shape quality evaluation, some new measures are defined.